2017
DOI: 10.1103/physrevd.96.023504
|View full text |Cite
|
Sign up to set email alerts
|

Chiral magnetohydrodynamic turbulence

Abstract: In this work the influence of the chiral anomaly effect on the evolution of magnetohydrodynamic turbulence was studied. We argue that before the electroweak symmetry breaking and for temperatures high enough such that the electron mass can be ignored, the description of a charged plasma in general needs to take into account the interplay between turbulence and the anomaly effects. It was demonstrated that this generalization can have important consequences on the evolution of turbulence, leading to the creatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 86 publications
1
47
1
Order By: Relevance
“…Note that different choices of evolution equations for µ 5 are possible, depending on the microscopic physics; see the discussion in Boyarsky et al (2015). In particular, an evolution equation for µ 5 with a damping term, −Γ f µ 5 , and a source term, Γ sr µ 5 , has recently been used by Pavlović et al (2017) to study the influence of the chiral anomaly on the evolution of MHD turbulence. Here Γ f is the total chirality flipping rate, and Γ sr is a source term that takes into account the generation of chiral asymmetry.…”
Section: Dynamic Equation For the Chiral Chemical Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that different choices of evolution equations for µ 5 are possible, depending on the microscopic physics; see the discussion in Boyarsky et al (2015). In particular, an evolution equation for µ 5 with a damping term, −Γ f µ 5 , and a source term, Γ sr µ 5 , has recently been used by Pavlović et al (2017) to study the influence of the chiral anomaly on the evolution of MHD turbulence. Here Γ f is the total chirality flipping rate, and Γ sr is a source term that takes into account the generation of chiral asymmetry.…”
Section: Dynamic Equation For the Chiral Chemical Potentialmentioning
confidence: 99%
“…This contribution to the electric current causes an instability in the system (Joyce & Shaposhnikov 1997) that has been analyzed in many works (Fröhlich & Pedrini 2000;Ooguri & Oshikawa 2012;Boyarsky et al 2012a;Kumar et al 2014;Grabowska et al 2015;Manuel & Torres-Rincon 2015;Buividovich & Ulybyshev 2016;Boyarsky et al 2015;). This instability may be relevant in the physics of the early universe (Joyce & Shaposhnikov 1997;Fröhlich & Pedrini 2000, 2002Semikoz & Sokoloff 2004;Semikoz et al 2009;Boyarsky et al 2012a,b;Semikoz et al 2012;Tashiro et al 2012;Dvornikov & Semikoz 2012, 2014Manuel & Torres-Rincon 2015;Gorbar et al 2016;Pavlović et al 2016;Pavlović et al 2017), of the quark-gluon plasmas (Akamatsu & Yamamoto 2013;Taghavi & Wiedemann 2015;Hirono et al 2015), or of neutron stars (Ohnishi & Yamamoto 2014;Dvornikov & Semikoz 2015a,b;Yamamoto 2016;Dvornikov 2016). However, to the best of our knowledge, a systematic analysis of the system of chiral MHD equations, including the back-reaction of the magnetic field on the chiral chemical potential and the coupling to the plasma velocity field, U (t, x) appears to be missing.…”
Section: Introductionmentioning
confidence: 99%
“…This instability has been a subject of intensive study in recent years [25,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. It is established that the growth of this instability is governed by the chiral anomaly equation.…”
Section: Application To Heavy-ion Collisionsmentioning
confidence: 99%
“…This idea was also used by Sigl [3][4][5] in the context of neutron star astrophysics, and one concluded that the amplification a e-mail: garcia@dft.if.uerj.br of the magnetic field is replaced actually by an attenuation of the magnetic field. By making use also of chiral QED in spacetimes with torsion (referring to work by de Sabbata and Gasperini [6]) one derived from the polarization of vacuum and electron-positron massive fermion pairs that the time component of the torsion axial vector term in the curl B equation induces the chiral term where indeed the electric current seems to be along the magnetic field.…”
Section: Introductionmentioning
confidence: 98%